Immunohistochemical evaluation of Sonic Hedgehog signaling pathway proteins (Shh, Ptch1, Ptch2, Smo, Gli1, Gli2, and Gli3) in sporadic and syndromic odontogenic keratocysts - Hoyos Cadavid, Ana Maria; Kaminagakura, E. [UNESP]; Rodrigues, M. F.S.D.; Pinto, C. A.L.; Teshima, T. H.N.; Alves, F. A. (Springer Nature, 2018)
Aims: The aim of this study was to compare the clinical and demographic features of 62 patients presenting sporadic odontogenic keratocysts (OKCs) or OKCs associated with nevoid basal cell carcinoma syndrome (NBCCS). In conjunction with this, we also evaluated the immunohistochemical expression of Shh, Ptch1, Ptch2, Smo, Gli1, Gli2 and Gli3 proteins in 86 OKCs. By doing this, we add to the understanding of the biology of this type of lesion, providing tools that will help facilitate the early diagnosis of NBCCS in those patients where the first manifestation is that of OKCs. Methods: This is a retrospective study; patients were classified into two groups: group 1 which consisted of those who were not affected by NBCCS (49 patients and 57 OKCs) and group 2 which consisted of those who were diagnosed with NBCCS (13 patients and 29 OKCs). The clinical and demographic features were studied and the immunohistochemical expression of Sonic Hedgehog proteins (Shh, Ptch1, Ptch2, Smo, Gli1, Gli2, and Gli3) was analyzed in all samples. Results: There was an increase in the expression of three proteins in the syndromic OKC, when compared to that of sporadic cysts. Shh and Gli1 showed higher cytoplasmic expression, while Smo revealed stronger nuclear and cytoplasmic expressions. Conclusion and clinical relevance: Our findings suggest that the expression patterns of important Shh pathway proteins can represent valuable markers for early diagnosis of NBCCS-associated OKCs, as the major criterion for the diagnosis of NBCCS is currently based on the late appearance of basal cellular carcinomas. Thus, standardizing a new diagnostic tool for diagnosis of NBCCS could be of great importance in the identification of therapeutic targets. We therefore suggest, as based on our findings, that OKCs showing high expression of Shh, Smo, and Gli1 are potentially associated with NBCCS.
Keywords: Nevoid basal cell carcinoma syndrome; Odontogenic cysts; Odontogenic keratocyst; Oral diagnosis; Sonic Hedgehog